A Multidisciplinary Approach in The Diagnosis of Allergic and Non-Allergic Respiratory Diseases: Nasal Cytology and Feno. - Peirolo Anna; Simoncini Daniela; Macchi Alberto; Graziani Daniela; Porcu Stefania; Nespoli Luigi (Journal of Otolaryngology Advances, 2015)
Upper and lower airway disease is a common condition. Its prevalence is increasing in different areas of the world, but, at present, non-allergic rhinitis is underestimated. The aim of this study was to investigate FeNO (fractional exhaled nitric oxide) and nasal cytology in allergic and non-allergic patients, in order to reach a correct diagnosis. This study was performed on 120 children with rhinitis and/or asthma, evaluated by an allergist and an otolaryngologist. Skin prick-test and nasal cytology were tested in all patients; FeNO only in the asthmatic ones. The proportion of positive results in nasal cytology was higher in non-allergic than in allergic children: 22 out of 23 patients, vs 91 out of 97 patients. A significant correlation was found between FeNO levels and increase in nasal eosinophil counts. There is compelling evidence of a close relationship between upper and lower airway in asthma and rhinitis. The presence of rhinitis should always be investigated in children with asthma; therefore, FeNO and nasal cytology have clinical benefit both in allergic and non-allergic children. Our finding also supports the use of nasal cytology to evaluate non-allergic rhinitis (NAR).
Keywords: nasal cytology